The impact of COVID-19 disease on the natural course of cirrhosis: Before and after starting vaccination - Keskin, Onur; Oral, Hakan; Sahin, Tevhide; Kav, Taylan; Parlak, Erkan (Frontiers in Medicine, 2023)
Background: Cirrhosis has been reported as an important risk factor for death in coronavirus disease 2019 (COVID-19) disease. In this study, we aimed to investigate the effects of COVID-19 on the natural course of cirrhosis before and after starting vaccination. Methods: The cirrhosis patients in our cohort (n: 140; median age:56; 71 female) were included in this study. The median MELD (Model For End-stage Liver Disease) score was 11(6–25) and CCI (Charlson Comorbidity Index) score was 4(1–11). In total, 85 had CTP (Child-Turcotte-Pugh)-A, 44 had CTP-B and 11 had CTP-C cirrhosis. The course of COVID-19 in this patient group was evaluated before and after COVID-19 vaccination. Results: Between March 2020 and January 2021, 36 of the 140 cirrhosis patients had developed COVID-19. Cirrhosis(+)/COVID-19(+) and Cirrhosis(+)/COVID-19(-) groups did not differ in terms of age, CCI and MELD-Na scores, or gender. There were six deaths in the Cirrhosis(+)/COVID-19(+) group and five in the Cirrhosis(+)/COVID-19(-) group (6/36[16.6%] vs 5/104[4.8%]; p:0.03). Patients who died were older, had higher CCI and MELD-Na scores, and lower albumin levels. Having had COVID-19 [6.45 (1.43–29.4); p: 0.015], higher MELD-Na score [1.35(1.18–1.60); p:0.001] and higher CCI score [1.65(1.14–2.39); p:0.008] were found to be independent predictors of mortality. After effective vaccination started in Turkey, only 11 of the remaining 129 patients developed COVID-19, and only one patient died, who was unvaccinated. Discussion: In our cirrhotic cohort, COVID-19 disease was associated with 16% mortality in the pre-vaccination period. COVID-19 vaccination prevents serious illness and death due to COVID-19 in cirrhotic patients.